BMP7 improves insulin signal transduction in the liver via inhibition of mitogen-activated protein kinases. Issue 2 (November 2019) - Ma, Hong; Yuan, Jin; Ma, Jinyu; Ding, Jie; Lin, Weiwei; Wang, Xinlei; Zhang, Mingliang; Sun, Yi; Wu, Runze; Liu, Chun; Sun, Cheng; Gu, Yunjuan
Abstract : Bone morphogenetic protein 7 (BMP7), a member of the transforming growth factor-β (TGF-β) family, plays pivotal roles in energy expenditure. However, whether and how BMP7 regulates hepatic insulin sensitivity is still poorly understood. Here, we show that hepatic BMP7 expression is reduced in high-fat diet (HFD)-induced diabetic mice and palmitate (PA)-induced insulin-resistant HepG2 and AML12 cells. BMP7 improves insulin signaling pathway in insulin resistant hepatocytes. On the contrary, knockdown of BMP7 further impairs insulin signal transduction in PA-treated cells. Increased expression of BMP7 by adenovirus expressing BMP7 improves hyperglycemia, insulin sensitivity and insulin signal transduction. Furthermore, BMP7 inhibits mitogen-activated protein kinases (MAPKs) in both the liver of obese mice and PA-treated cells. In addition, inhibition of MAPKs recapitulates the effects of BMP7 on insulin signal transduction in cultured hepatocytes treated with PA. Activation of p38 MAPK abolishes the BMP7-mediated upregulation of insulin signal transduction both in vitro and in vivo . Together, our results show that hepatic BMP7 has a novel function in regulating insulin sensitivity through inhibition of MAPKs, thus providing new insights into treating insulin resistance-related disorders such as type 2 diabetes.